2021
DOI: 10.2334/josnusd.20-0338
|View full text |Cite
|
Sign up to set email alerts
|

Influence of single post, oval, and multi-post restorative techniques and amount of residual tooth substance on fracture strength of endodontically treated maxillary premolars

Abstract: The aim of this study was to compare the influence of the number of coronal walls and post-endodontic restorations on the mechanical strength of 165 recently extracted endodontically treated maxillary premolars. Methods: The teeth were divided into 3 control (no post) and 3 test groups according to the number of residual walls. Each test group was divided into subgroups according to the type of post-endodontic restoration (single, oval, and multi-post techniques). Samples were prepared conforming to the assign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Out of 17 subgroups, the load inclination applied was 90° for nine [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and 30°/45° for eight [ 19 , 20 , 21 , 22 , 23 , 24 ]. PDL simulation was performed in five subgroups [ 10 , 12 , 15 , 22 , 25 ] while thermocycling was applied in five [ 10 , 12 , 15 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Out of 17 subgroups, the load inclination applied was 90° for nine [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and 30°/45° for eight [ 19 , 20 , 21 , 22 , 23 , 24 ]. PDL simulation was performed in five subgroups [ 10 , 12 , 15 , 22 , 25 ] while thermocycling was applied in five [ 10 , 12 , 15 , 23 , 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…Out of 17 subgroups, the load inclination applied was 90° for nine [ 10 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] and 30°/45° for eight [ 19 , 20 , 21 , 22 , 23 , 24 ]. PDL simulation was performed in five subgroups [ 10 , 12 , 15 , 22 , 25 ] while thermocycling was applied in five [ 10 , 12 , 15 , 23 , 26 ]. Tip diameter was respectively lower than 2 mm and between 2 and 3 mm in one group, between 3 and 5 mm in four groups, 6 mm in seven groups and 8 mm in two groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some studies supported the utilizing of accessory or a multiple fiber post technique to increase the fracture resistance of severe tooth structure loss or wide canal endodontically treated teeth. 8,16,17 The resin composite core materials have also been recommended for luting endodontic posts, especially in a flared canal due to their high strength, simplicity, and homogeneity of using the same material for the post and core placement. It was reported that resin composite core materials combined with an adhesive system is a comparable, and in some ways superior, method for luting endodontic posts compared to the resin cement.…”
Section: Introductionmentioning
confidence: 99%
“…A thick layer of the resin cement induces air bubbles, shrinkage stresses, and predisposes the post to debonding. Therefore, some studies supported the utilizing of accessory or a multiple fiber post technique to increase the fracture resistance of severe tooth structure loss or wide canal endodontically treated teeth 8,16,17 . The resin composite core materials have also been recommended for luting endodontic posts, especially in a flared canal due to their high strength, simplicity, and homogeneity of using the same material for the post and core placement.…”
Section: Introductionmentioning
confidence: 99%